The effect of foreign direct investment on the economic growth of Sub-Saharan African countries: An empirical approach - Belesity Bekalu Ayenew (Cogent Economics & Finance, 2022)
The impact of foreign direct investment on the host country's economic growth has been a source of debate in past theoretical and empirical investigations. The PMG/ARDL model, which has a practical advantage in examining the effect of foreign direct investment in the short and long run, has received little attention in prior empirical investigations. This study investigates the effect of foreign direct investment on the economic growth of Sub-Saharan African countries. The study examined panel data from 22 nations in Sub-Saharan Africa from 1988 to 2019. The PMG/ARDL model was used to look at the short- and long-term effects of foreign direct investment on economic growth. The panel unit root test and panel co-integration test were employed to improve the model's estimation. According to the findings, in the long run, foreign direct investment has a favorable and significant effect, but it is statistically insignificant in the short run. The study concludes that foreign direct investment boosts long-term economic growth. As a result, countries in Sub-Saharan Africa should focus on attracting foreign direct investment.
Keywords: F21; F43; O40; O47; 330; Foreign direct investment; economic growth; pooled mean group; effect; SubSaharan Africa